2007
DOI: 10.1523/jneurosci.3728-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Extracellular Signal-Regulated Kinase in Maintaining Long-Term Memory-Relevant Excitability Changes

Abstract: Pyramidal neurons in the piriform cortex from olfactory-discrimination-trained rats show enhanced intrinsic neuronal excitability that lasts for several days after learning. Such enhanced intrinsic excitability is mediated by long-term reduction in the postburst afterhyperpolarization (AHP), which is generated by repetitive spike firing. AHP reduction is attributable to decreased conductance of a calciumdependent potassium current, the sI AHP . We have previously shown that such learning-induced AHP reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 49 publications
(86 reference statements)
4
64
0
Order By: Relevance
“…Here too, there is a mild increase in the activity level in the pseudo-trained group. As previously shown (Cohen-Matsliah et al 2007), the activity level of ERK in the total homogenate fraction, which is known to mediate many cellular events, is not enhanced after learning. This compartment-specific ERK activation, next to the cell membrane, supports the notion of its possible modulation of learning-induced synaptic transmission.…”
Section: Erk Activation Modifies Synaptic Transmission Only After Leasupporting
confidence: 55%
See 3 more Smart Citations
“…Here too, there is a mild increase in the activity level in the pseudo-trained group. As previously shown (Cohen-Matsliah et al 2007), the activity level of ERK in the total homogenate fraction, which is known to mediate many cellular events, is not enhanced after learning. This compartment-specific ERK activation, next to the cell membrane, supports the notion of its possible modulation of learning-induced synaptic transmission.…”
Section: Erk Activation Modifies Synaptic Transmission Only After Leasupporting
confidence: 55%
“…Previous studies have shown that olfactory learning-induced long-lasting enhancement of neuronal excitability is dependent on long-term persistent activation of a second messenger cascade that includes ERK and PKC (Cohen-Matsliah et al 2007). Here we show that these two key enzymes have also a pivotal role in maintaining learning-induced long-lasting enhancement of synaptic connectivity, as reflected by PPF reduction measured 3 d after learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such rule learning is accompanied by a series of pre-and postsynaptic cellular modifications in layer II pyramidal neurons of the piriform cortex. Long-term enhancement occurs in the three components controlling neuronal activation: the excitatory synaptic drive mainly mediated by glutamate receptors (Knafo et al 2005;Saar et al 1999Saar et al , 2002, the intrinsic neuronal excitability (Cohen-Matsliah et al 2007;Saar et al 1998Saar et al , 2001, and synaptic inhibition mediated by GABA A receptors (Brosh and Barkai 2009). These modifications are widespread throughout the piriform cortex network; physiological and morphological modifications are found in most of the studied neurons (Brosh and Barkai 2009;Knafo et al 2005;Saar et al 1998Saar et al , 1999Saar et al , 2002Saar and Barkai 2003).…”
mentioning
confidence: 99%